2021
DOI: 10.1021/acsinfecdis.0c00565
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Brugia malayi Calreticulin Protein Generates Robust Antiparasitic Immunity and Offers Protection during Experimental Lymphatic Filariasis

Abstract: Lymphatic filariasis causes permanent and long-term disability worldwide. Lack of potent adulticidal drugs, the emergence of drug resistance, and the nonavailability of effective vaccines are the major drawbacks toward LF elimination. However, immunomodulatory proteins present in the parasite secretome are capable of providing good protection against LF and thus offer hope in designing new vaccines against LF. Here, we evaluated the immunogenicity and protective efficacy of B. malayi calreticulin protein (BmCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Flow-sorted Cont. rEos, TPE rEos, and TPE iEos ( n = 50,000) were incubated in separate tubes in the presence of FITC-dextran (1 mg/mL) for 2 h in a 5% CO 2 incubator set at 37 °C, and the increase in FITC fluorescence was measured using flow cytometry, as described previously. ,, …”
Section: Methodsmentioning
confidence: 99%
“…Flow-sorted Cont. rEos, TPE rEos, and TPE iEos ( n = 50,000) were incubated in separate tubes in the presence of FITC-dextran (1 mg/mL) for 2 h in a 5% CO 2 incubator set at 37 °C, and the increase in FITC fluorescence was measured using flow cytometry, as described previously. ,, …”
Section: Methodsmentioning
confidence: 99%
“…Other parasites whose Calr has displayed the capacity to inhibit the complement pathway include, Trypanosoma carassii ( 70 ), E. histolytica ( 16 ), E. dispar ( 71 ), Brugia malayi ( 72 , 73 ), Wuchereria bancrofti ( 19 ), Trichinella spiralis ( 20 , 74 ), O. viverrini ( 75 ), Haemonchus contortus ( 76 , 77 ), Necator americanus ( 76 , 78 ), S. mansoni and S. japonicum ( 79 ), among others. An apparent exception to this rule is found in the Calr of the tick Amblyomma americanum , which is present in the saliva of the specimen.…”
Section: Parasite Calreticulin and The Complement Systemmentioning
confidence: 99%
“…Yadav et al. ( 19 ) inoculated mice with recombinant Calr from B. malayi (rBmCalr), the causative agent of lymphatic filariasis (also known as elephantiasis). It was shown that rBmCalr activated peritoneal macrophages and splenocytes stimulated the production of cytokines characteristic of the Th1 response, such as IL-6, IL-2, IFN-γ and TNF-α.…”
Section: Calreticulin-based Parasite Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors declare no competing interests. 16,33,[94][95][96][97][98][99][100][101] , compared to a more diffuse pattern of expression for proteins identified in secretome studies (teal) 31,32 . (D) Heatmap of gene expression patterns shows head-enrichment of candidate vaccine targets, as well as both head-and body-enrichment for the targets of antifilarial drugs (benzimidazoles: β-tubulins, macrocyclic lactones: GluCls, and emodepside: BK channel).…”
Section: Data Availabilitymentioning
confidence: 99%